Vehicular Technology Conference. IEEE 55th Vehicular Technology Conference. VTC Spring 2002 (Cat. No.02CH37367)
DOI: 10.1109/vtc.2002.1002684
|View full text |Cite
|
Sign up to set email alerts
|

Comparative forward link traffic channel performance evaluation of HDR and 1XTREME systems

Abstract: This paper presents a comparison of the forward link performance of the RDR and lXTREME systems. Both systems have been proposed as possible evolutionary paths for the 1.25-MHz cdma2000 system [I], and have been designed to enable high data rate packet transmission.Link-level performance is evaluated by chip-level time-domain simulation of the forward data traftlc channel in the presence of additive white Gaussian noise, and is then used in a system-level simulator modeling a network of 19 three-sector cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Shadowing is modeled as log-normal distributed random variable, which means that the logarithm of received signal amplitude is normally distributed. There are mathematical conditions which need to be satisfied in order to assume that the envelope is log-normally distributed, but for this simulation, we assume that all the conditions are satisfied [9]. Log-normal shadowing is created using Gudmonson approach [7].…”
Section: Channel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Shadowing is modeled as log-normal distributed random variable, which means that the logarithm of received signal amplitude is normally distributed. There are mathematical conditions which need to be satisfied in order to assume that the envelope is log-normally distributed, but for this simulation, we assume that all the conditions are satisfied [9]. Log-normal shadowing is created using Gudmonson approach [7].…”
Section: Channel Modelmentioning
confidence: 99%
“…Shadowing between AT and different sectors of the same base station is assumed 100% correlated, and shadowing between AT and different sectors of different base stations is assumed 50% correlated.Small scale fading is assumed that it is Rayleigh distributed. It is created using filtered white Gaussian noise approach [9]. We dropped users at one of the sectors of the center base station.…”
Section: Channel Modelmentioning
confidence: 99%
“…This scheduler is implemented in High Data Rate (HDR) networks of CDMA2000-IX. It is recently studied by many authors as those of [28], [29], and [30]. Their research showed unevenness in the data rates achieved by different users when they experience different channel conditions in terms of the corresponding fading properties.…”
Section: Ofdm Signal Processingmentioning
confidence: 99%